1987
DOI: 10.1227/00006123-198704000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Intracarotid Chemotherapy with 1,3-Bis-(2-chloroethyl)-1-nitrosourea (BCNU) in 5% Dextrose in Water in the Treatment of Malignant Glioma

Abstract: After radiotherapy, 20 patients, 18 with documented progression of malignant glioma and 2 with Grade II astrocytoma, received a total of 52 courses of intracarotid 1,3-bis-(2-chloroethyl)-1-nitrosourea (BCNU) at a dose of 150 mg/m2 dissolved in 5% dextrose in water. The patients were treated at 6-week intervals for a maximum of five courses of chemotherapy per patient. Response to treatment was analyzed on computed tomographic scans by measuring the volume of the enhancing tumor and any central low density. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In our series two patients suffered a decrease in visual acuity in the eye ipsilateral to the mannitol- [7-10, 13, 24]. Because of the various protocols used at the different centers, it is difficult to make formal comparisons, and it appears that the incidence of visual changes in these series is in keeping with or less than that of intra-carotid therapy in general [3,17,24,25].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In our series two patients suffered a decrease in visual acuity in the eye ipsilateral to the mannitol- [7-10, 13, 24]. Because of the various protocols used at the different centers, it is difficult to make formal comparisons, and it appears that the incidence of visual changes in these series is in keeping with or less than that of intra-carotid therapy in general [3,17,24,25].…”
Section: Discussionmentioning
confidence: 86%
“…In addition,neuro-oncologists have become concerned with the increasing problem, of postradiation neurotoxicity, either with or without adjuvant chemotherapy. Johnson et al reported their experience with intra-arterial BCNU in 20 patients receiving the drug after 'tumor recurrence' [3]. They contend that patients have less toxicity and survive longer if intra-arterial BCNU is not given immediately after radiation, but is delayed until tumor recurs.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have evaluated a nitrosourea derivative or a platinum analog. Several investigators have evaluated the activity of single-agent IA carmustine [19,20,43,44]. Greenberg et al [19] evaluated the response of 24 patients with recurrent tumors to intracarotid carmustine (200-300 mg/m 2 every 6-8 weeks).…”
Section: Treatmentmentioning
confidence: 99%
“…Clinical studies in the 1980s and 1990s found improved response rates with IA therapy (especially BCNU) in patients with primary and metastatic brain tumors [4][5][6][7][8][9][10][11]. Renewed interest in this form of therapy was based upon the predictions of the theoretical pharmacokinetic modeling.…”
Section: Introductionmentioning
confidence: 99%